Antimicrobial Activities of Essential Oils of Different Pinus Species from Bosnia and Herzegovina - Snježana Mirković; Vanja Tadić; Marina T. Milenković; Dušan Ušjak; Gordana Racić; Dragica Bojović; Ana Žugić (MDPI AG, 2024)
Background/Objectives: The emergence of antimicrobial resistance has urged researchers to explore new antimicrobial agents, such as essential oils (EOs). The aim of this study was to examine chemical composition and antimicrobial activity of the EOs from the needles and green cones of four Pinus species (Pinus mugo Turra., P. nigra J.F., P. syilvestris L., and P. halepensis Miller) from Bosnia and Herzegovina. Methods: Chemical profiles of EOs were assessed by gas chromatography, while microdilution method was used to test their antimicrobial activity. A synergistic action of EOs and gentamicin was investigated by the checkerboard assay. Results: The chemical composition of the tested EOs showed a high percentage of α-pinene, (E)-caryophyllene, limonene, germacrene D, myrcene, and δ-3-carene. EO from green cones of P. sylvestris showed high efficiency against S. aureus and E. faecalis. The MIC of P. nigra cones' EO was 100 μg/mL against E. coli. The EO of P. halepensis green cones demonstrated the strongest activity against E. faecalis. EOs of P. halepensis needles and green cones exhibited the highest activity against C. albicans. Further, synergistic interaction was detected in combination of the selected EOs/gentamicin toward S. aureus and K. pneumoniae. Conclusions: Among the tested EOs, oils of P. sylvestris cones and P. halepensis cones and needles showed the greatest antimicrobial activity. The same EOs and EO from P. nigra cones displayed synergistic potential in combination with gentamicin, supporting their utilization as antimicrobial agents alone or in combination with antibiotics, which is in line with their ethnopharmacological usage and circular bioeconomy principles.